Проблемы изучения английского языка в условиях дошкольной организации - Нурханова, Ж.К. (My University, 2016)
Preschool age is especially favorable for the beginning of learning English, children of this age are particularly sensitivity to linguistic phenomenon. In this article, given the different types of work on the study of the English language.
Keywords: multilinguism; intensively; integrated classes